2011
DOI: 10.1159/000331719
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia Induces Closure of Gap Junctional Channels and Opening of Hemichannels in Heart-derived Cells and Tissue

Abstract: Aim: Gap junction intercellular communication (GJIC) and hemichannel permeability may have important roles during an ischemic insult. Our aim was to evaluate the effect of ischemia on gap junction channels and hemichannels. Methods: We used neonatal rat heart myofibroblasts and simulated ischemia with a HEPES buffer with high potassium, low pH, absence of glucose, and oxygen tension was reduced by dithionite. Microinjection, western blot, immunofluorescence, cell viability and dye uptake were used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…Moreover, they are triggered to open by some stimulation, such as inflammation, mechanical stress or ischemia (Batra et al, 2012;Johansen et al, 2011;Karpuk et al, 2011). In our study, however, we demonstrated for the first time that connexin-mediated hemichannels are responsible for glucose uptake in OPCs, implying a role for oligodendroglial connexin hemichannels under physiological conditions.…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationmentioning
confidence: 48%
“…Moreover, they are triggered to open by some stimulation, such as inflammation, mechanical stress or ischemia (Batra et al, 2012;Johansen et al, 2011;Karpuk et al, 2011). In our study, however, we demonstrated for the first time that connexin-mediated hemichannels are responsible for glucose uptake in OPCs, implying a role for oligodendroglial connexin hemichannels under physiological conditions.…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationmentioning
confidence: 48%
“…A naturally occurring cytoplasmic C-terminal fragment of Cx43, ~20 kDa in size, has been described and characterized in cultured murine and hamster cells and after Cx43 overexpression in human HeLa cells [7]. Others have also reported Cx43 immunoreactive bands of ~20 kDa, such as in glioma cells [8] and in neonatal rat heart myofibroblasts [9]. A 20-kDa Cx43 immunoreactive band is also clearly detected in zebrafish heart 48 hours postfertilization [10], and the authors also noted an ~30-kDa band in zebrafish ovaries.…”
Section: Resultsmentioning
confidence: 99%
“…This study confirms that blockade of connexin hemichannel opening by Gap26 confers protection to intact heart against ischemia-reperfusion injury regardless of the administration before or after the occurrence of ischemia (Hawat et al, 2010). Another study also shows that opening of Cx43 hemichannels during ischemia-reperfusion appears to be an important mechanism for ischemia-reperfusion injury in the heart given that Gap26 significantly reduces the infarct/risk ratio (Johansen et al, 2011). However, the alternative hemichannel, pannexin channel is not involved.…”
Section: Connexin Hemichannelsmentioning
confidence: 99%